Quantifying potential yield and yield gaps of soybean using CROPGRO-soybean model in the humid tropics of southwestern Ethiopia - Mekonnen, A.; Getnet, M.; Nebiyu, A.; Abebe, A.T. (Springer, 2022)
In the past, much of the emphasis on soybean research in Ethiopia has been on the development and testing of new varieties and classical agronomic trials with limited use of crop models that help in estimating the potential yield and yield gaps, and identifying the most important barriers of achieving optimal yield. CROPGRO-soybean model is an important tool for estimating the potential yield and yield gaps of soybean under various management and environmental conditions. The objectives of this study, therefore, were to evaluate the performance of the model and quantify the potential yield, water-limited yield, and yield gaps of soybean in the humid environments of southwestern Ethiopia. The model calibration and evaluation were done with a field experiment conducted on sowing dates of Clark 63 k and SCS-1 soybean verities in 2019 and 2020. Model evaluation results revealed that the simulated phenological stages, growth, and yield of the two soybean varieties were in good agreement with the corresponding measured values. The evaluated model was used to quantify potential yield, water-limited yield, and yield gaps. The actual yield was obtained by averaging four districts’ annual production data from 2014 to 2018 and survey data collected at the end of the 2019 and 2020 growing seasons. The mean actual yield for the dominantly cultivated soybean variety, Clark 63 k, was 1689 kg ha−1; whereas the highest simulated potential yield and water-limited yields were 3632 kg ha−1 and 3455 kg ha−1, respectively. The yield gap due to water-limited ranged from 5 to 52% of the potential yield. Similarly, the yield gap percentage due to factors other than water-limited ranged from 7 to 51%. This percentage can be regarded as high relative to the efforts made to improve soybean productivity through varietal improvement in Ethiopia. Our findings show that poor distribution of rainfall and low night temperature during the reproductive stages of the crop due to delayed planting, and suboptimal use of row spacing represent the major causes of large yield gap percentage in the target area. The results of this study, therefore, revealed the importance of adopting optimum planting date in humid areas in maintaining the productivity gain achieved through varietal improvement. We suggest that adopting early planting date (between May 22 and June 7) and optimum row spacing (40 cm) help to enhance productivity and reduce yield gaps in soybean. In conclusion, the CROPGRO-soybean model can serve as a useful tool for quantifying the potential yield and yield gaps, and identify appropriate strategies that may help in increasing soybean productivity in Ethiopia.